1918
DOI: 10.1007/bf01827772
|View full text |Cite
|
Sign up to set email alerts
|

Übertragungsversuche mit spitzem Kondylom

Abstract: (Prag).Ffir die Entstehung der spitzen Kondylome sind bekanntlich verschiedene Ursachen verantwortlich gemacht worden.Seitdem erkannt wurde, da~ sie mit Lues nichts zu tun haben und auch nicht als eine Folgekrankheit der Gonorrhoe anzusehen sind, stehen sich eigentlich nur mehr zwei Anschauungen bezfiglich ihrer Entstehung gegenfiber. Von der einen Se, ite wird behauptet, da~ sie infolge yon Irritation der Haut oder Schlehnhaut durch Sekrete oder durch mechanische Momente, also als Folge 5rtlicher Reize sich e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
2

Year Published

1933
1933
2007
2007

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…Extracts of a penile condyloma that was harvested from a young medical student who did not exhibit other overt symptoms of venereal diseases were used to inoculate sites on the forearms of the author and his assistant as well as the genital mucosa of a "virgo intacta." After a period of 2.5 months, the unfortunate female subject developed genital condyloma, and flat warts appeared on the forearms of two male probands (139). These and other experiments led to the realization that genital warts represent distinct disease entities that are caused by a transmissible agent.…”
mentioning
confidence: 97%
“…Extracts of a penile condyloma that was harvested from a young medical student who did not exhibit other overt symptoms of venereal diseases were used to inoculate sites on the forearms of the author and his assistant as well as the genital mucosa of a "virgo intacta." After a period of 2.5 months, the unfortunate female subject developed genital condyloma, and flat warts appeared on the forearms of two male probands (139). These and other experiments led to the realization that genital warts represent distinct disease entities that are caused by a transmissible agent.…”
mentioning
confidence: 97%
“…To prove a common viral cause for skin and genital warts by this means, it would be necessary to inoculate successfully a cell-free filtrate of genital warts into the skin, and of skin warts into the genitals; the use of unfiltered extracts would not be acceptable, as living cells might be introduced and act as a tissue graft (Gross, 1961). Unfiltered penile wart extracts have raised skin warts on several occasions (Waelsch, 1918;Frey, 1924; Goldschmidt and Kligman, 1958), but filtered extracts only once (Serra, 1924). Vulval wart extracts have never been used; and the crucial experiment of successfully inoculating an extract of skin warts into the genitals has never been carried out.…”
mentioning
confidence: 99%
“…In 1907 Ciuffo demonstrated that a filterable agent is able to induce hand warts [10]. Similar experiments were later performed for condylomas by Waelsch [67]. With the introduction of electron microscopy, virus particles were identified in extracts of hand warts and condylomas.…”
mentioning
confidence: 87%